ORNAMEN JEPARA SEBAGAI STRUKTUR BENTUK SET MEJA KAFE - Arfan Abdullah; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2020)
Along with the times and the busy routine of humans every day humans will not be separated from the desire to pamper themselves or refresh or seek entertainment so that they are free from both physical and entertainment tensions, seeing from that also develops places for humans to just relax and find a refreshing atmosphere. diatana these places in the form of a cafe or mini restaurant To create a comfortable atmosphere so that cafe or mini restaurant visitors get the comfort of a cafe or mini restaurant manager, it is necessary to design a space or location in such a way, including furniture for customers to relax, including a set of cafe tables that must be comfortable to occupy and create a pleasant atmosphere.After seeing and paying attention to the conditions desired by visitors, then the writer carried out the design process by utilizing Jepara ornaments as a form of cafe table so that new designs emerged to compete in the growing furniture industry and created a different cafe or miniresto concept.